A new Stachys species from Turkey: Stachys siirtensis (Lamiaceae) - Güner, Özal; Akçi̇çek, Ekrem; Di̇rmenci̇, Tuncay (Phytotaxa, 2021)
Stachys siirtensis (Lamiaceae), a new endemic species from Botan Valley of Siirt province in Turkey, is here described. The species is characterized by having congested verticillasters. Hairiness, calyx and corolla length, as well as nutlet and the arrangement of verticillasters, have been used to distinguish Stachys species. Stachys siirtensis is morphologically similar to S. ballotiformis and S. kurdica. The new species resembles S. ballotiformis, but it can be distinguished by flowering stems with glabrous to sparsely and retrorsely pubescence, longer calyx (8–10 mm long) and corolla (13–15 mm long). It also differs from S. kurdica by stalked glandular flowering stems, congested verticillasters, having pilose and sessile glands on calyx, and oblong-obovoid nutlets.